Positional Preferences and Narcissism: Evidence from “Money Burning” Dictator Games - Adam Ayaita; Kerstin Pull (Applied Economics Letters, 2020)
We study the relationship between positional preferences (i.e., preferences concerning the relative rank or position in comparison to others) and narcissism. We distinguish two dimensions of narcissism: Narcissistic admiration captures self-enhancement through searching for being admired, and narcissistic rivalry captures self-defense through an antagonistic orientation toward others. We use six “money burning” mini-dictator games to measure positional preferences. Controlling for other relevant individual characteristics such as the Big Five personality traits and gender, we find evidence that narcissistic admiration is a negative predictor and narcissistic rivalry a positive predictor of positional preferences. We further find exploratory evidence that studying business or economics as a major (vs. minor) subject is associated with less positional preferences and that the relationships between narcissism and positional preferences are mediated by decision makers' expectations with regard to other players' choices.
Keywords: A12; A13; D01; D63; 330; narcissism; narcissistic admiration; narcissistic rivalry; positional concerns; positional preferences; relative concerns